Micropipette Manipulation for the Production and Characterisation of Microparticles in Biomaterials Discovery - Henshaw, Charlotte A (2023)
The use of microparticles for biological applications is increasing, and with it, the need for specialised microparticles. While one of the major advantages of microparticles is the ability to fine-tune properties, such as chemistry and morphology to best serve an application, achieving this usually relies on lengthy trial-and-error processes. Micropipette manipulation techniques have proven to be valuable tools in studying cell mechanics, protein dehydration and material characterisation. The techniques permit the study of simple and complex multicomponent systems from an alternative perspective to traditional techniques. Utilising these techniques droplets and particle forming systems can be studied on the microscale and in real time. Thus, providing improved understanding of microparticle formation and aiding in particle design and optimisation. The hypothesis for this work was that micropipette manipulation techniques can be employed to understand and improve formation of bio-instructive microparticles. In this thesis, micropipette manipulation techniques were used to study a series of microparticle systems. To better enable this application, methods were developed to improve or extend existing analysis practices. The new routines allowed for a reduction in measurement error to the limit of detection, improved efficiency, and increased processing capabilities. Additionally new methods were developed for analysing droplet microstructure. A comprehensive assessment of the impact of the most widely utilised microparticle materials, poly(vinyl alcohol) (PVA) and poly(D, L lactic acid) (PDLLA), on solvent/water interfaces was conducted using the static equilibrium interfacial tension method. The polymers were treated as additives to two solvent/water combination base systems (dichloromethane (DCM) and ethyl acetate.) From this assessment empirical equations were derived for calculating the interfacial tension for given concentrations of the polymers. The maximum interfacial tension for DCM/water to remain as stable drops during particle formation was determined as approximately 11.1 mN m-1. Droplet dissolution was assessed for both base solvents with a range of PDLLA/PVA concentrations. The diffusion coefficients for the base solvents in water were 17 ± 3.8 x10-6 cm2 s-1 (DCM) and 10.1 ± 0.28 x10-6 cm2 s-1 (ethyl acetate). Negligible change was seen for the addition of polymer to either phase. Comparisons to the Epstein-Plesset model and the activity-based model for dissolution were conducted for both solvents for the range of PDLLA concentrations concerned. Dissolution followed the curve of the Epstein-Plesset model but deviated from the expected final size given by the activity-based dissolution model. A series of novel, bio-instructive surfactants were assessed for their use in particle formation through the polymerisation of monomer droplets produced using droplet microfluidics. The effectiveness of the different surfactants was determined using static equilibrium interfacial tension measurements. Different core monomers, polymer architecture and hydrophilic and hydrophobic components were considered. Optimum concentrations of surfactants were taken into droplet microfluidics for optimised particle production. Flow maps were generated mathematically using the optimised compositions and showed good agreement with the stable regions found experimentally. Investigations of material transfer between the monomer drop and the surroundings showed unusual behaviour by the monomer for which a mechanism is proposed to explain such behaviour. A dual surfactant system for enabling the production of biodegradable microparticles using droplet microfluidics was investigated and the concentrations optimised for performance and application criteria. The particles produced using PDLLA in ethyl acetate formed secondary droplets both inside and on the surface of drop as dissolution occurred. By varying the concentrations of surfactant, core polymer and continuous phase saturation, the morphology of these particles could be manipulated. Using EGPEA-mPEGMA it was possible to generate a topography, reproducible between single particles studies and high volume microparticle production, that could be controlled by adjusting surfactant concentration. The studies presented here demonstrate the improved understanding of selected microparticle formation systems through the application of micropipette manipulation techniques. Characterisation of novel biomaterials was conducted which in turn allowed the optimisation of bio-instructive microparticles through droplet microfluidics.